Improving Children's Discipline Through the Method of Giving Assignments in Group A of Al-Khairaat Kindergarten Kayu Malue Ngapa - Fatmawati, Fatmawati; Setianingsih, Hesti Putri; Awalunisah, Sita; Nurhayati, Nurhayati (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
The problem in the research is that the discipline of children in group A of Al-Khairaat Kindergarten Kayu Malue Ngapa has not developed as expected. The purpose of the research is to improve children's discipline by using the method of giving assignments to group A of Al-Khairaat Kindergarten Kayu Malue Ngapa. This research is a classroom action research, the research subjects are 15 children in group A of Al-Khairaat Kindergarten Kayu Malue Ngapa consisting of 6 boys and 9 girls. After taking action, the results of this study can be concluded that through giving assignments can improve children's discipline, it is proven that there is an increase in the ability from cycle I to cycle II of children coming to school on time in the BSB and BSH categories from 40.00% to 80.00% (40.00%), the ability of children in doing assignments given in the BSB and BSH categories from 46.67% to 80.00% (33.33%), then the ability of children who are terrible in following learning with the BSB and BSH categories from 40.00% to 86.66% (46.66%). In general, there is an average increase of 40.00% from cycle I to cycle II, although there are still children whose discipline has not increased but only around 6.67% of each aspect observed.